Handel’s use of plucked instruments - Fraga, Orlando (Música em Perspectiva, 2012)
Three central features of Baroque music encompass a large portion of questions about the performance of this particular repertory: its improvisatory aspect, the use of basso continuo, and the instrumental color and variety. Teorbo and lute solos, aside of playing a role as a continuo, filled in the intermissions of oratorios in Italy since late 17th century, while organ concertos provided the same function for English oratorios in the early 18th century. It is from Handel’s early period ‒ his first trip to Italy in 1707 ‒ that teorbo and archiliuto start to appear in his vocal music. Handel employed either the teorbo or archiliuto (or simply liuto) in twelve vocal works and in one instrumental Ouverture. A complete examination of the circumstances that involve this particular aspect of Handel’s music is the subject this paper.